The Correlation Between Non-Hodgkin Lymphoma and Expression Levels of B-Cell Activating Factor and Its Receptors - shen, xianjuan; wang, mei; guo, yuehua; ju, shaoqing (Advances in clinical and experimental medicine : official organ Wroclaw Medical University, 2016)
Lymphoma is a malignant tumor of the immune system originating from lymph nodes and extralymphatic tissues. Its occurrence is believed to be associated with various immune cells due to the proliferation and differentiation of lymphocytes during the immune response. It has been found in many studies that B-cell activating factor (BAFF), as a member of the tumor necrosis factor (TNF) superfamily, could specifically activate B lymphocytes and promote their proliferation. To explore correlations between non-Hodgkin lymphoma (NHL) and the expression of BAFF and its receptors in NHL patients. The protein expression of BAFF and its receptors in serum and BAFF mRNA expression in peripheral blood mononuclear cells (PBMCs) of 47 NHL patients and 20 healthy subjects were detected by ELISA and RFQ-PCR and compared with LDH and β2M levels. BAFF mRNA expression in the PBMCs of NHL patients was significantly higher than in healthy controls. The expression levels of serum BAFF and the three receptors (TACI, BCMA and BAFF-R) in NHL patients were significantly higher than in healthy controls, and were not significantly correlated with β2M and LDH levels. The serum protein concentration of BAFF and the expression level of BAFF mRNA in PBMCs of NHL patients underwent abnormal changes, indicating that BAFF and its receptors may play some role in the pathogenesis of NHL.